If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + -3t) + -1(-3) + 2 = 0 (4 * 2 + -3t * 2) + -1(-3) + 2 = 0 (8 + -6t) + -1(-3) + 2 = 0 Multiply -1 * -3 8 + -6t + 3 + 2 = 0 Reorder the terms: 8 + 3 + 2 + -6t = 0 Combine like terms: 8 + 3 = 11 11 + 2 + -6t = 0 Combine like terms: 11 + 2 = 13 13 + -6t = 0 Solving 13 + -6t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -6t = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -6t = 0 + -13 -6t = 0 + -13 Combine like terms: 0 + -13 = -13 -6t = -13 Divide each side by '-6'. t = 2.166666667 Simplifying t = 2.166666667
| ((x/4)+(4*x))/(x/7)=56.7 | | T/45+2/11=-4/11 | | sqrt(363ab^5c^7)= | | 16=d-12/4 | | 2(3x-10)=4 | | 6x+21=16x-51 | | 4x+9=18- | | 3x-2+22=40 | | 4w^2=-9w-2 | | -2(-z+8)+3z=29 | | -(x-5)=m(4-5x) | | 129+.25x=216.50 | | 5x-20=85 | | 6+6x=20+2x | | 6(d-5)+7= | | 4+5ln(x)=8 | | -2(-2+8)+3z=29 | | 8=-3w+0.5-3w+4.3 | | 4xn=15-120 | | 2(5x+2)=2x+14+3x | | x-5/4+3=-3x-4/5 | | x+2=0.25x-4 | | P/5-2=24 | | -6=v-2 | | -4xp+m=8-2p | | -6+w=-2 | | 0.35w=-7 | | 64-3n=5n | | 4-x^2-7x=0 | | 3x^5/7 | | -4b+44=-4(b-11) | | 45-9g=36g |